2006
DOI: 10.1111/j.1475-6773.2006.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Searches the Internet for Health Information?

Abstract: Populations with serious health needs and those facing significant barriers in accessing health care in traditional settings turn to the Internet for health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
223
5
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(256 citation statements)
references
References 16 publications
18
223
5
5
Order By: Relevance
“…support their self-management, 16,17 and some now turn to online resources as a primary source of information. 18,19 These tools augment patients' self-care activities (a fundamental goal of health informatics technology) 20 by improving organization, providing information, and enhancing communication. Moreover, patients who use these resources report increased health-related knowledge and a greater sense of empowerment to improve their health.…”
Section: Introductionmentioning
confidence: 99%
“…support their self-management, 16,17 and some now turn to online resources as a primary source of information. 18,19 These tools augment patients' self-care activities (a fundamental goal of health informatics technology) 20 by improving organization, providing information, and enhancing communication. Moreover, patients who use these resources report increased health-related knowledge and a greater sense of empowerment to improve their health.…”
Section: Introductionmentioning
confidence: 99%
“…It is important for healthcare professionals, specifically physicians, to be proactive and to refer families to evidencebased websites following a diagnosis. This referral could save time, support the patient-health care professional relationship, and prevent the negative consequences associated with poor quality health information 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Many families rely on the Internet to look for information and understand their health issues 14,15 , especially in relation to chronic conditions 15 . The quality of the information found on the internet can be highly variable, and therefore it has been suggested that health professionals should be proactive in directing families to high quality, evidence-based sources 16 , and provide feedback on information their patients discover on the internet 17,18 .…”
mentioning
confidence: 99%
“…É mais provável que um indivíduo acometido por uma patologia busque informações sobre saúde na rede do que um indivíduo sadio (nettleton, 2004;BeRGeR et al, 2005;BundoRF et al, 2006). Portadores de patologias consideradas estigmatizantes (depressão, incontinência urinária, herpes, entre outras) encontram no anonimato das relações virtuais um caminho, pois a possibilidade de falar sobre suas queixas aumenta consideravelmente com a comunicação à distância, tanto com médicos quanto com outros indivíduos portadores de quadros semelhantes.…”
Section: A Internet Como Recursounclassified